2017
DOI: 10.1002/adma.201606663
|View full text |Cite
|
Sign up to set email alerts
|

Superior Stable and Long Life Sodium Metal Anodes Achieved by Atomic Layer Deposition

Abstract: Na-metal batteries are considered as the promising alternative candidate for Li-ion battery beneficial from the wide availability and low cost of sodium, high theoretical specific capacity, and high energy density based on the plating/stripping processes and lowest electrochemical potential. For Na-metal batteries, the crucial problem on metallic Na is one of the biggest challenges. Mossy or dendritic growth of Na occurs in the repetitive Na stripping/plating process with an unstable solid electrolyte interpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
246
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 296 publications
(252 citation statements)
references
References 36 publications
6
246
0
Order By: Relevance
“…Energy Mater. Figure 4c summarizes the elemental contents of the surface of PGM-T and Al 2 O 3 /PGM-5, which shows that Al 2 O 3 / PGM-5 has less sodium and fluorine which mainly originate from the decomposition of NaOTf, [61,63] consistent with the CV results discussed above. Figure 4c summarizes the elemental contents of the surface of PGM-T and Al 2 O 3 /PGM-5, which shows that Al 2 O 3 / PGM-5 has less sodium and fluorine which mainly originate from the decomposition of NaOTf, [61,63] consistent with the CV results discussed above.…”
supporting
confidence: 81%
“…Energy Mater. Figure 4c summarizes the elemental contents of the surface of PGM-T and Al 2 O 3 /PGM-5, which shows that Al 2 O 3 / PGM-5 has less sodium and fluorine which mainly originate from the decomposition of NaOTf, [61,63] consistent with the CV results discussed above. Figure 4c summarizes the elemental contents of the surface of PGM-T and Al 2 O 3 /PGM-5, which shows that Al 2 O 3 / PGM-5 has less sodium and fluorine which mainly originate from the decomposition of NaOTf, [61,63] consistent with the CV results discussed above.…”
supporting
confidence: 81%
“…In their results, the ALD Al 2 O 3 ‐protected Li can prevent Li metal corrosion in electrolyte and reduce the dendrite growth as well, which further enhances electrochemical performance with elevated capacity and longer lifetimes. Very recently, our group also successfully demonstrated the protection of Na metal anode using ALD Al 2 O 3 , yielding extended life time and reduced growth of parasitic sodium dendrites . Molecular layer deposition (MLD), as an analogy of ALD, can be employed to produce pure polymeric thin films or inorganic–organic hybrid thin films, which can hold many advantages such, as lower growth temperatures, tunable thermal stability, and improved mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…These features make ALD an ideal technique for Na anode protection . Recently, both our group and Hu et al have successfully demonstrated the application of ALD Al 2 O 3 coating layers for the enhancement of electrochemical stability of Na metal anode and suppressed dendrite growth with prolong cycling life time in carbonate and ether based electrolyte systems, respectively . Furthermore, our group first reported the use of inorganic–organic coating (alucone) via molecular layer deposition as a protective layer for metallic Na anode .…”
Section: Introductionmentioning
confidence: 93%